Assessment of polygenic risk of hypertension - A. S. Limonova; A. I. Ershova; A. V. Kiseleva; V. E. Ramensky; Yu. V. Vyatkin; V. A. Kutsenko; A. N. Meshkov; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2023)
Hypertension (HTN) is a leading risk factor for the development of cardiovascular diseases. In recent decades, the rapid development of genetic tests, in particular genome-wide association study (GWAS), has made it possible to identify hundreds of nucleotide sequence variants associated with the development of HTN. One approach to improve the predictive power of genetic testing is to combine information about many nucleotide sequence variants into a single risk assessment system, often referred to as a genetic risk score. Within the framework of this review, the most significant publications on the study of the genetic risk score for HTN will be considered, and the features of their development and application will be discussed.